Pandangan Ulama Muhammadiyah dan Ulama Nahdlatul Ulama Kabupaten Garut Tentang Justtifikasi Riba di Perbankan - Syaik Abdillah; Ai Nurmayanti (Jurnal Hukum Ekonomi Syariah, 2026)
Differences of opinion regarding the legality of bank interest in Islam have become a significant issue in the modern economic system, particularly in conventional banking practices. From the Islamic perspective, bank interest is often associated with riba, which is explicitly prohibited in the Qur’an. However, amid differing interpretations, various justifications have emerged among scholars. This study aims to examine the views of Muhammadiyah and Nahdlatul Ulama (NU) scholars in Garut Regency concerning the justification of riba in conventional banking transactions. This research employs a qualitative method with a literature study approach and in-depth interviews with scholars from both organizations. Data were obtained through documentation and direct interviews with Muhammadiyah and NU figures in Garut. The findings reveal both similarities and differences in the perspectives of the two groups of scholars. Both agree that bank interest in private banking is categorized as riba and thus prohibited (haram). However, regarding state-owned banks, Muhammadiyah scholars tend to classify it as syubhat (doubtful), while NU scholars consider it permissible (halal) since the profits are redirected for the benefit of the community. This study highlights the importance of understanding scholarly differences in examining Islamic economic law and underscores the urgency of dialogue between scholars and banking practitioners in formulating solutions that align with Sharia principles. Keywords: Riba; Conventional Banking; Muhammadiyah; Nahdlatul Ulama; Justification